Percepção coletiva em um espaço público de lazer: o caso da praça do Operário no bairro de São Brás em Belém do Pará - GOMES, Benielton Cássio Vieira (2023)
In this paper, a case study was made in Praça do Operário, a collective environmental perception of people in relation to the public space, often seen as inhospitable or unpleasant. Through research on impressions and interviews made with people from the city of Belém in two ways, the first composed of people who found the square and the second by people who were not in Praça do Operário. The objective was to track the opinion profile of two groups, and comparatively understand how the environmental impact/ use space is perceived in contrast to people who, despite living in the city, do not use such close contact with space to only Then, we conclude with an analysis of uses space as a possibility for leisura. All this while analyzing and comparing with other squares of the city of Belém.